Pengaruh Keteladanan Guru dan Orang Tua terhadap Sikap Kejujuran Siswa SMK Klaten, Jawa Tengah - Mulyati, Mulyati; Hidayati, Mega; Hariyanto, Muhsin (Center of Language and Cultural Studies, 2020)
This study analyzes the influence of teachers' and parents' role model on students' honest behavior both partially and simultaneously. The study used a survey design with descriptive correlation to which the quantitative approach was applied. The sample of this study is 40 students of Senior Vocational School in Kalten, Central Java, Indonesia selected at random. Data were collected using questionnaires and were analyzed using multi-linear regression. Results show that teachers' role model has a positive significant influence on students' honest behavior. In addition, the parents role model has a positive significant influence on students' honest behavior, and simultaneously, teachers and parents role model has positive significant on students honesty behavior.